Violence Exposure Is Associated With Atypical Appraisal of Threat Among Women: An EEG Study - Perizzolo Pointet, Virginie Chloé; Moser, Dominik Andrea; Vital, Marylène; Rusconi Serpa, Sandra; Todorov, Alexander; Schechter, Daniel Scott (Frontiers in Psychology, 2021)
Introduction: The present study investigates the association of lifetime interpersonal violence exposure (IPV), related posttraumatic stress disorder (IPV-PTSD), and appraisal of the degree of threat posed by facial avatars. Methods: We recorded self-rated responses and high-density electroencephalography (HD-EEG) among women, 16 of whom with lifetime IPV-PTSD and 14 with no PTSD, during a face-evaluation task that displayed male face-avatars varying in their degree of threat as rated along dimensions of dominance and trustworthiness. Results: The study found a significant association between lifetime IPV exposure, under-estimation of dominance and over-estimation of trustworthiness. Characterization of EEG microstates supported that lifetime IPV-PTSD modulates emotional appraisal, specifically in encoding and decoding processing associated with N170 and LPP evoked potentials. EEG source localization demonstrated an overactivation of the limbic system, in particular the parahippocampal gyrus, in response to non-threatening avatars. Additionally, dysfunctional involvement of attention-related processing anterior prefrontal cortex was found in response to relatively trustworthy avatars in IPV-PTSD individuals compared to non-PTSD controls. Discussion: This study showed that IPV exposure and related PTSD modulate individuals’ evaluation of facial characteristics suggesting threat. Atypical processing of these avatar characteristics were marked by group differences in brain regions linked to facial processing, emotion regulation and memory.